Sustainable nutrition perceptions and professional recommendations of Turkish nutrition and dietetics students: a qualitative focus group study - Neslihan Öner; Aynur Çetinkaya; Hasan Durmuş; Elif Kocaağalar Akince; Yağmur Yaşar Fırat; Arda Borlu (BMC Medical Education)
Abstract Background Nutrition and dietetics students are instrumental in fostering sustainable eating behaviors at both individual and community levels. Addressing knowledge gaps and strengthening their role as change agents is essential to promote a sustainable future. This qualitative study aimed to explore nutrition and dietetics students' perceptions of sustainable nutrition and their professional recommendations for enhancing social awareness. Methods Using a qualitative research design, data were collected through focus group interviews conducted between September and October 2022. A purposive sampling strategy was used to ensure representation of diverse views by selecting 20 students from various classes in the nutrition and dietetics program who had not been previously educated in sustainable nutrition. Focus group interviews lasting 60–80 min were conducted, and content analysis was used to identify the main themes. Results Three primary themes emerged from the analysis: Conceptual Meaning (mentioned 24 times), Determinants: Environmental Health (mentioned 31 times), and the Role of Dietitians (mentioned 27 times). Although students demonstrated awareness of sustainable nutrition, many perceptions were surface level, highlighting the need for enhanced curriculum focus on this topic. Conclusions As future dietitians, these students are uniquely positioned to influence individual and collective dietary habits, fostering improvements in both human and planetary health. This research identifies gaps in their understanding and underscores the critical role of dietitians in advocating for sustainable practices. By addressing these gaps, the study contributes to the development of effective educational interventions. The findings provide valuable insights into future dietitians' attitudes toward sustainable diets, which may guide public health strategies that integrate environmental and nutritional perspectives, as well as inform curriculum development and professional training programs.